The Impact of Financial Performance on Stock Prices of Sub-Coal Production Mining Companies Listed on the Indonesia Stock Exchange (IDX) 2020–2022 - Puspita, Dewi; Syamsuddin, Syamsuddin; Hasan, Asriani (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
Financial performance is a depiction or assessment of the effectiveness, efficiency, and success of an organization, particularly a company, in managing and optimizing financial resources over a specific period. This study aims to examine the effect of the Current Ratio (CR), Return on Equity (ROE), and Debt to Equity Ratio (DER) on the stock prices of coal production sub-industry mining companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2022 period. This research employs a quantitative method. The sampling technique used in this study is purposive sampling. The data used in this study is secondary data, including financial reports and stock prices obtained from www.idx.co.id. The study utilizes partial linear regression analysis using SmartPLS version 4.0.9.9 software. The results of this study indicate that the Current Ratio (CR) variable does not have a significant effect on stock prices. Furthermore, the Return on Equity (ROE) variable significantly affects stock prices with a significance value of 0.007 < 0.05. Lastly, the Debt to Equity Ratio (DER) variable does not have a significant effect on stock prices.